Capacity Building of Cassava Silkworm Cultivation Group with the Application of Spinning Machine and Identification of Ungkrung Content - Subrata, Arsyad Cahya; Sudarmini, Sudarmini; Ibdal, Ibdal; Suharto, Totok Eka; Sutikno, Tole; Wulandari, Erika (Jurnal Abdimas, 2024)
Silk fabric is still one of the exclusive fabrics sought after, especially by women. However, at the end of this decade, silk fabric production decreased. The decreasing availability of silk fabric raw materials influences the decline in silk fabric production. The availability of raw materials for silk fabric cannot be separated from the number of silkworms (Bombyx mori L.) cultivated as a cocoon producer which is later spun into silk yarn.  Gunung Sewu is a silkworm cultivation group based in Rongkop District, Gunungkidul Regency, Yogyakarta, which has successfully conditioned silkworms to consume rubber cassava leaves as their main feed. Currently, sales of cultivation products are still in the form of ready-spun cocoons and fried ungkrung (inside of cocoons). The silk fabric factory is also willing to buy cocoons that have been spun into silk thread at a higher price. However, the Gunung Sewu group does not yet own a spinning wheel, so it cannot carry out the spinning process independently. On the other hand, derivative products in the form of ungkrung are still processed by frying. Even though there are still many foods that can be developed from silkworm ungkrung processed ingredients. In this community empowerment program, Gunung Sewu group capacity-building activities were carried out by applying spinning machines and identifying the content of ungkrung. The results obtained from the spinning machine application activity were that the turnover of the Gunung Sewu silkworm cultivation group increased by 200%. While the activity of identifying the content of ungkrung showed a significant increase in the knowledge of group members.